Opinion: How to transform food systems to feed the world and prevent mass extinctions - Fan, Shenggen (2019)
Food systems are comprised of the many elements that add up to the ways people get their food – the farms where food is produced, the businesses that process food into products, the markets and restaurants where it is sold and consumed, the policies that shape every step of the process, and much more. While the world has been able to supply more food, energy, and materials to people in most places, this continues to take a toll on the ability to do so in the future. Nature is crucial for food, feed, energy, medicines, and other materials central for human well-being, yet food systems contribute up to 29 percent of all greenhouse gas emissions and continue to overuse scarce natural resources, contributing to the loss of biodiversity and animal and plant species. Without urgent action, we will not achieve the UN Sustainable Development Goals, or global climate goals. Taking a food systems approach to ensure human and planetary health at all stages along the food value chain will be critical. Several areas can be prioritized for policy action.